PENERAPAN EVIDENCE BASED NURSING INTERVENSI STORYTELLING DENGAN MEDIA FINGER PUPPET UNTUK MENGATASI ANSIETAS PADA ANAK USIA PRASEKOLAH AKIBAT HOSPITALISASI - Niasa Lora Rimar (2022)
Anxiety is a person's emotional response that is influenced by the subconscious and often has no specific cause. Anxiety can affect a child's development and quality of life. Anxiety due to hospitalization causes stressors for children. The purpose of writing to provide an overview of nursing care for preschool-aged children who experience anxiety due to hospitalization and the influence of innovative storytelling interventions with finger puppet to overcome the anxiety of preschoolaged children at Bhayangkara Tk.1 Hospital R. Said Sukanto. Storytelling therapy has benefits in developing imagination so that it can help children find ways to deal with anxiety. The number of respondents involved in this study amounted to 2 people with 1 person being given the intervention while 1 other person was not given the intervention. Measurement of anxiety scores using the Hamilton Anxiety Rating Scale (HARS) questionnaire in patients with family assistance . Storytelling therapy using finger puppet media is carried out once a day for 15-20 minutes along with giving injection drugs. The implementation was carried out for 3 days and got an anxiety score on the first day of 26 (moderate anxiety) and on the third day it decreased to 19 (mild anxiety) which indicates the influence of storytelling therapy with finger puppet media on decreasing anxiety scores of preschool-aged children.